Long‐Term Observations of Nitrogen and Phosphorus Export in Paired‐Agricultural Watersheds under Controlled and Conventional Tile Drainage. Issue 5 (1st September 2015) - Sunohara, M. D.; Gottschall, N.; Wilkes, G.; Craiovan, E.; Topp, E.; Que, Z.; Seidou, O.; Frey, S.K.; Lapen, D. R.
Abstract : Controlled tile drainage (CTD) regulates water and nutrient export from tile drainage systems. Observations of the effects of CTD imposed en masse at watershed scales are needed to determine the effect on downstream receptors. A paired‐watershed approach was used to evaluate the effect of field‐to‐field CTD at the watershed scale on fluxes and flow‐weighted mean concentrations (FWMCs) of N and P during multiple growing seasons. One watershed (467‐ha catchment area) was under CTD management (treatment [CTD] watershed); the other (250‐ha catchment area) had freely draining or uncontrolled tile drainage (UCTD) (reference [UCTD] watershed). The paired agricultural watersheds are located in eastern Ontario, Canada. Analysis of covariance and paired t tests were used to assess daily fluxes and FWMCs during a calibration period when CTD intervention on the treatment watershed was minimal (2005–2006, when only 4–10% of the tile‐drained area was under CTD) and a treatment period when the treatment (CTD) watershed had prolific CTD intervention (2007–2011 when 82% of tile drained fields were controlled, occupying >70% of catchment area). Significant linear regression slope changes assessed using ANCOVA ( p ≤ 0.1) for daily fluxes from upstream and downstream monitoring sites pooled by calibration and treatment period were −0.06 and −0.20 (stream water) (negative values represent flux declines in CTD watershed), −0.59 and −0.77 (NH4 + –N), −0.14 and −0.15 (NO3 – –N), −1.77 and −2.10 (dissolved reactive P), and −0.28 and 0.45 (total P). Total P results for one site comparison contrasted with other findings likely due to unknown in‐stream processes affecting total P loading, not efficacy of CTD. The FWMC results were mixed and inconclusive but suggest physical abatement by CTD is the means by which nutrient fluxes are predominantly reduced at these scales. Overall, our study results indicate that CTD is an effective practice for reducing watershed scale fluxes of stream water, N, and P during the growing season. Core Ideas: Paired watershed study evaluates conventional and control drainage impacts at watershed scale. Controlled tile drainage imposed en masse at watershed scales reduces stream, nitrate, ammonium, and dissolved reactive P fluxes during the growing season. Total P fluxes in stream were shown to reduce and increase depending on location in watershed.